1996
DOI: 10.1063/1.471490
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic properties of quinizarin chemisorbed on alumina

Abstract: A comparative theoretical study of atomic hydrogen adsorption on the (110) faces of Al, Cu, Ni, and NiAl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…We consider (0001) surface of a-alumina with Al termination as the filler surface, which is the most stable one [29][30][31]. Fig.…”
Section: Modeling Of System and Inter-atomic Potentialsmentioning
confidence: 99%
“…We consider (0001) surface of a-alumina with Al termination as the filler surface, which is the most stable one [29][30][31]. Fig.…”
Section: Modeling Of System and Inter-atomic Potentialsmentioning
confidence: 99%
“…28,29 We consider (0001) surface of a-alumina as the filler surface, which is the most stable one when terminated with Al. [30][31][32] As depicted in Fig. 2, a thin a-alumina slab of 120 atoms with (0001) surface is placed in the rectangular parallelepiped of L x ; L y ; L z ð Þ¼ ð14:0Å; 8:2Å; 7:0ÅÞ; the vacuum layer with z-depth 20 Å is added on the (0001) surface.…”
Section: Modeling Of System and Preparation Of Inter-atomic Potenmentioning
confidence: 99%
“…Previous calculations performed for dye molecules adsorbed on g-alumina have shown that the (110) surface may be adequately modelled by small clusters containing 1-3 Al atoms [28][29][30]. The following requirements regarding the minimum cluster size for a specific adsorption site is that all the nearest neighbors of aluminum ions should be included in the ϩ cluster model used for the (110) surface of g-alumina (H s refers to the atoms used for the saturation of dangling bonds and H n those used for the methoxyl ion/cluster charge neutralization).…”
Section: Determination Of the Cluster Model Of The G -Aluminamentioning
confidence: 99%